Báo cáo giải trình, tiếp thu, chỉnh lý dự thảo Luật Đường bộ (Kèm theo Báo cáo tóm tắt) - Ủy ban Thường vụ Quốc hội (2024)
Toàn văn Báo cáo giải trình, tiếp thu, chỉnh lý dự thảo Luật Đường bộ (Kèm theo Báo cáo tóm tắt).